Progression of Mild to Moderate Stenosis in the Internal Carotid Arteries of Patients With Ischemic Stroke - Ong, Cheung-Ter; Wong, Yi-Sin; Sung, Sheng-Feng; Wu, Chi-Shun; Hsu, Yung-Chu; Su, Yu-Hsiang; Hung, Ling-Chien (Frontiers in Neurology, 2018)
Background and purpose Severe stenosis in the internal carotid artery may increase the risk of ischemic stroke. The factors that affect the progression of carotid artery stenosis in patients with ischemic stroke are poorly studied. No guidelines for the duration of follow-up of patients with ischemic stroke through carotid ultrasonography exist. Methods In this retrospective study, 179 patients (108 men; mean age, 68 years) with ischemic stroke and mild to moderate stenosis in the internal carotid artery (ICA) were recruited. Carotid artery ultrasonography was performed over the period of January 2013 to June 2016 with a median follow-up of 36 months (mean 36.5  3.5 months). The severity of carotid artery stenosis was estimated with the following equation: 1 − (narrowest ICA diameter/total lumen diameter at the narrowest site). The severity of stenosis was categorized into grades I (0%–29%), II (30%–49%), III (50%–59%), and IV (60%–69%). The patient’s stenosis grade was defined on the basis of the stenosis rate of the ICA side with most severe stenosis. Results Stenosis progressed in 17.9% (64/358) of the vessels in 30.7% (55/179) of patients. The risk of stenosis progression increased as the severity of ICA stenosis increased. Patients with stenosis rates of above 50% are at a higher risk of stenosis progression than those with stenosis rate of <50%. Relative to the patient group with an ICA stenosis rate of 0%–29%, the adjusted odds ratios of stenosis progression were 2.33 (p = 0.03; 95% CI: 1.05~5.17), 3.50 (p = 0.09; 95% CI: 0.81~15.84), and 6.61 (p = 0.03; 95% CI: 1.01~39.61) in patient groups with ICA stenosis rates of 30%–49%, 50%–59%, and 60%–69%, respectively. Hyper-LDL-cholesterolemia (Hyper-LDL-c) also increased the risk of stenosis progression, with an adjusted odds ratio of 2.22 (p = 0.03; 95% CI: 1.05~4.71). Conclusion The rate of ICA stenosis progression increases with stenosis grade. Patients with ICA stenosis severity >50% and Hyper-LDL-c have high rates of stenosis progression. For the patients with stroke and ICA stenosis severity >50%, annual follow up through carotid artery ultrasonography may be necessary.